2006
DOI: 10.1111/j.1600-0501.2005.01242.x
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable polylactide membranes for bone defect coverage: biocompatibility testing, radiological and histological evaluation in a sheep model

Abstract: Large bony defects often show a delayed healing and have an increasing risk of infection. Several materials are used for the coverage of large defects. These materials must be biocompatible, easy to use, and must have an appropriate stability to present a mechanical hindrance. Aim of this study was to investigate two different biodegradable membranes for defect coverage in a sheep model. Round cranial defects (1.5 cm diameter) were created in sheep. Six different treatments were investigated: defects without m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 19 publications
2
27
1
Order By: Relevance
“…Enhanced remodeling of the spongiosa into native bony under the membranes could be detected in cranial defects but also without an osteopromoting effect. In contrast to our study, a foreign body reaction around the tested membranes was observed in sheep [73]. …”
Section: Discussioncontrasting
confidence: 99%
“…Enhanced remodeling of the spongiosa into native bony under the membranes could be detected in cranial defects but also without an osteopromoting effect. In contrast to our study, a foreign body reaction around the tested membranes was observed in sheep [73]. …”
Section: Discussioncontrasting
confidence: 99%
“…These membranes have first been not absorbable [32,158,159] and then adsorbable [33,160,161,162], bringing to two types of clinical application, the Guided Tissue Regeneration (GTR) and the Guided Bone Regeneration (GBR). It is one of the most fertile fields of applied clinical research and the recent introduction of the use of nanomaterials [78,163] has led to further advances: on the one hand, the use of nanopowders [164] but above all the development of periodontal membranes, both for GTR and GBR, obtained by nanotechnological methods such as film-casting [165,166,167], dynamic filtration [168] or electrospinnig [169,170].…”
Section: Experimental Studies In Dentistry With the Use Of Nanomatmentioning
confidence: 99%
“…However, although systematic comparisons between the in vitro and in vivo behaviors of ENPBs are important before they are evaluated in the clinic, such comparisons were not made in our previous work Polymer materials have been widely used as biomedical materials. [27][28][29][30][31] Many synthetic polymer biomaterials similar to P(DLLA-CL), such as PDLLA, [32][33][34][35] PLGA, 36-37 P(LLA-CL), 38 and PCL, [39][40] have been assessed in vivo to determine their behaviors in the bone microenvironments of sheep, [32][33][35][36] rabbit, 34,37 and pig. [38][39][40] However, there have been no reports evaluating the in vivo behaviors of P(DLLA-CL) biomaterials in bone microenvironments thus far.…”
Section: Introductionmentioning
confidence: 99%